Eddy‐Induced Acceleration of Argo Floats - Wang, Tianyu; Gille, Sarah T.; Mazloff, Matthew R.; Zilberman, Nathalie V.; Du, Yan (Journal of Geophysical Research: Oceans, 2020)
Float trajectories are simulated using Lagrangian particle tracking software and eddy‐permitting ocean model output from the Estimating the Circulation and Climate of the Ocean, Phase II (ECCO2) project. We find that Argo‐like particles near strong mean flows tend to accelerate while at their parking depth. This effect is pronounced in western boundary current regions and in the Antarctic Circumpolar Current system. The acceleration is associated with eddy‐mean flow interactions: Eddies converge particles toward regions with stronger mean currents. Particles do not accelerate when they are advected by the eddy or mean flow alone. During a 9‐day parking period, speed increases induced by the eddy‐mean flow interactions can be as large as 2 cm s−1, representing roughly 10% of the mean velocity. If unaccounted for, this acceleration could bias velocities inferred from observed Argo float trajectories. Plain Language Summary Ocean instruments called floats are carried by ocean currents. Tests carried out using output from a numerical simulation of the ocean show that near strong currents, eddies tend to bump floats into the currents. As a result, on average, at the end of a 10‐day sampling period, a float is likely to end up in water that is moving faster than the water where it started 10 days earlier. This effect should be considered when using particles to estimate mean velocities.